Experimental Analysis of the Influence of the Application of TiN, TiAlN, CrN and DLC1 Coatings on the Friction Losses in an Aviation Internal Combustion Engine Intended for the Propulsion of Ultralight Aircraft - Piotr Wróblewski (MDPI AG, 2021)
Currently, there are many methods of reducing the friction losses of the main components of an internal combustion piston engine. The operating conditions of internal combustion piston engines intended for the propulsion of ultralight aircraft differ significantly from those prevailing in the case of using these engines for the propulsion of vehicles. There are many studies on the influence of selected anti-wear coatings on the friction coefficients when using various lubricants, measured via tribometers. Unfortunately, the conditions obtained in the laboratory significantly differ from those prevailing in an engine operating under external conditions. The study investigated the influence of a change in the tribological parameters of TiN, TiAlN, CrN and DLC1 anti-wear coatings on the moment of resistance to the piston movement of an aircraft engine. The operating parameters of a real engine working in an aircraft were simulated. The main focus was on the coating layers of the sliding surfaces of the piston rings and the cylinder running surface. The properties of the coatings affect the correlation of the scale of the adhesion and cohesion phenomena of the oil to the opposite planes, and this determines the nature of the changes in the moment of resistance to engine motion. As it is commonly known, with an increase in the value of the maximum pressure of the working medium in the combustion chamber, the share of mixed friction in liquid friction increases, similar to the high oil temperatures occurring in aircraft engines. Therefore, there is a justified need to supplement the research in the field of analyzing the characteristics of the torque of resistance to motion for these engines, in particular in the field of the usable rotational speeds of the crankshaft. Applicable anti-wear systems based on selected coatings can significantly improve operational safety and noticeably reduce fuel consumption.